Optical velocimetry based on the spatial correlation of off-axis image speckle patterns - Pomarico, Juan (1997)
A method is proposed for measuring the linear velocity of a moving rough surface. It is based on maximizing the spatial correlation between two laterally shifted image speckle patterns. Besides, an expression of a spatially variant point-spread function is given, which modifies the spatial distributions of the off axis image speckle patterns.